Dependence structure between world crude oil prices: Evidence from NYMEX, ICE, and DME markets - T. Kiatmanaroch (2018)
© 2014 by the Mathematical Association of Thailand. All rights reserved. This paper examines the dependence structure between world crude oil prices using the D-vine copula based GARCH model to analyze three random variables, namely, Light crude futures 1-Pos (NYMEX), Brent crude futures 1- Pos (ICE), and Oman crude futures 1-Pos (DME). We find that NYMEX–ICE, NYMEX–DME, and ICE–DME have relatively strong dependence. In addition, we find the evidences for asymmetric tail dependence in each pair with the values of upper tail and lower tail dependences of three pair-copulas as being quite close to each other. Therefore, our findings support the "one great pool" hypothesis. Moreover, the results from the D-vine copula model indicate that the ICE is an important variable that governs the interactions in the dependence structure between the NYMEX and the DME. In other words, the change in the oil price of the ICE will impact quite significantly the prices of the NYMEX and the DME.